2014
DOI: 10.1002/mabi.201400052
|View full text |Cite
|
Sign up to set email alerts
|

Mussel‐Inspired Cell‐Adhesion Peptide Modification for Enhanced Endothelialization of Decellularized Blood Vessels

Abstract: Enhanced endothelialization of tissue-engineered blood vessels is essential for vascular regeneration and function of engineered vessels. In this study, mussel-inspired surface chemistry of polydopamine (pDA) coatings are applied to functionalize decellularized vein matrix (DVM) with extracellular matrix-derived cell adhesion peptides (RGD and YIGSR). DVMs engineered with pDA-peptides enhance focal adhesion, metabolic activity, and endothelial differentiation of human endothelial progenitor cells (EPCs) derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…Previous studies suggested that PDA can effectively promote NP–cell interactions on various polymer‐modified surfaces . The potential explanation for this increased NP–cell interactions ability was that the catechol groups of the compound can act as an immobilization site to bind with amino‐ or thiol‐functionalized biomolecules of the cell membrane or cell adhesive moieties in the extracellular matrix . Therefore, we can also assume that the catechol group of our AmQu may be the reason for the observed promoted NP–cell interactions and cellular internalization.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies suggested that PDA can effectively promote NP–cell interactions on various polymer‐modified surfaces . The potential explanation for this increased NP–cell interactions ability was that the catechol groups of the compound can act as an immobilization site to bind with amino‐ or thiol‐functionalized biomolecules of the cell membrane or cell adhesive moieties in the extracellular matrix . Therefore, we can also assume that the catechol group of our AmQu may be the reason for the observed promoted NP–cell interactions and cellular internalization.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the RGDS motif, other adhesive ligands such as the laminin derived YIGSR (Tyr-Ile-Gly-Ser-Arg) sequence [22,23] have been shown to promote EC adhesion and migration without enhancing platelet adhesion [24]. For instance, this peptide has enhanced the adhesion of ECs in hydrogels [13,25], PET [26], polyurethane [27,28], poly(2-hydroxyethyl methacrylate) [29] and decellularized scaffolds [30]. Finally, another cell adhesive sequence found in fibronectin, the REDV (Arg-Glu-Asp-Val) peptide, which targets ECs via the integrin ␣4␤1, has been reported to selectively promote EC adhesion and spreading over SMCs and platelets [22,31].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there has been a corresponding increase in the study of decellularized tissue modification to enhance endothelialization and reduce thrombogenicity. In attempts to accelerate endothelialization, researchers have coated decellularized grafts with VEGF, VEGF hydrogels, integrin ligands, and cell adhesion peptides [1923]. Other groups have chosen to focus on decreasing graft thrombogenicity.…”
Section: Introductionmentioning
confidence: 99%